Engineering synthetic and natural vesicular system for tumor-targeted drug delivery - Rayamajhi, Sagar (Kansas State University, 2021)
Nanomedicine provides exciting opportunities to solve modern-world medical problems from disease diagnosis to therapy. From the first approved nanomedicine in 1995 against cancer, Doxil®, to the recent sensation, lipid nanoparticle-based mRNA vaccine against COVID-19, nanomedicine has come a long way to the state of becoming a platform medical technology. Toward this endeavor, this dissertation is focused on lipid-based vesicles systems, synthetic liposomes, and cell-secreted extracellular vesicles (EVs), where we have explored and optimized efficient engineering techniques to achieve tumor-targeted drug delivery and diagnostic capacity. Liposomes are synthetic vesicles with an aqueous core and phospholipid bilayer and EVs are natural vesicles secreted by cells with protein-lipid bilayer and aqueous core carrying cellular information in terms of proteins and nucleic acid (mRNA, miRNA, DNA). These complementary properties when paired make them highly efficient delivery vehicles in a biological environment, an overarching goal of this dissertation. The main objective of this dissertation is to overcome two major challenges in nanoparticulate drug delivery system: 1) how to overcome endosome degradation of nanoparticles and maximize intracellular bioavailability and 2) how to overcome biological barriers for efficient delivery- rapid immune clearance, circulation stability, epithelial barriers, microenvironment barriers, cellular, and intracellular barriers. Toward this aim, we engineered a pH-sensitive liposome with pH-responsive 3ß-[N-(N',N'-dimethylaminoethane)-carbamoyl] (DC) moiety to avoid endosomal degradation. pH-sensitive liposome showed pH-responsive cationic properties which elevated the fusogenic characteristic of liposome at the acidic environment in the endosomes and facilitate endosomal escape via membrane fusion (Chapter 3). Although the in-vitro results were promising, the challenge to overcome the biological barrier remains. To overcome this problem, a natural messenger of the cellular system, which has been optimized with years of evolution, EVs, was used. We optimized a simple, efficient, and reproducible EVs isolation method by combining centrifugation, ultrafiltration, and size exclusion-based chromatography. Synthetic liposomes were used to engineer an EVs-based hybrid system that contributed to increasing overall yield, stability, and added functionality (Chapter 4). EVs derived from mouse macrophage J774A.1 showed preferential interaction toward cancer cells, both in vitro and in vivo mouse models showing promises for tumor-targeted drug delivery. Further, a gadolinium incorporated liposome was synthesized and hybridized with EVs to engineer a hybrid system with diagnostic capacity, which showed contrast-enhanced diagnostic characteristics as confirmed by clinical magnetic resonance imaging (Chapter 5). Finally, EVs were optimized for their reproducibility of physicochemical and functional properties. Rigorous EVs isolation technique and characterization confirmed the EVs production is significantly higher in cancer cells compared to non-cancer (Chapter 6). The nanosystems engineered in this study were successful to overcome endosomal degradation via escape, have longer retention time, good biocompatibility, efficient drug loading capacity, and tumor targeting characteristic, all of which are excellent properties for drug delivery systems. With this proof of concept and design consideration, this dissertation adds an important understanding of the vesicles-based system for tumor-targeted drug delivery. We envision that future works on the molecular mechanism behind the achieved biomimicry and tumor targeting potential can lead toward the translation of a vesicle-based system for tumor-targeted drug delivery.
Keywords: Extracellular vesicles; Nanomedicine; Drug delivery; Liposomes; Cancer